Monitoring the distribution of parks and land cover changes along the Tigris River using spatial analysis techniques - Abdullah Albakri Sundus A.; Kadhim Zina F.; Gburi Sura I.; Samer Muhend K.; Mohammed Faisel G. (E3S Web of Conferences)
Tilis study examines the use of GIS and Remote Sensing in monitoring vegetation growth of Baghdad in Al-Risafa limited hi the region Abu Nawas that alignment Tigris River. The various land features of land for the adopted area were be analyzed by spatial analysis techniques, Classification the images of land sat 8 will be considered. The techniques of classification that adopted in this work; including supervised with unsupervised techniques that are commonly used to produce land cover features. The results produced from the NDVI images gave a good indication of vegetation degradation through the period (2019 - 2023). For year 2019 the area of Rare plant 269100 m2. Low plant 603000 m2. and the medium plant was 344700 m2 total. Found that plant less area, and low plant area increases through the period (2019-2023) years. That is indicates decrease m vegetation area in the region of Abu Nawas with the decreasing rate of medium plant (12.6-8.3). These results can be due several reasons, including cimiate change, which causes a rise in temperatures and pollution in the waters of the Tigris River due to water scarcity and lack of interest in plowing the river on a regular basis, as well as due to tuban growth represented by the large number of vertical buildings that impede air access to plants and humans alike. The parks proposed hi this study, based on spatial analysis techniques depending on the classification methods, were distributed according to the selected sites, and their area ranged along the Tigris River between (172893 m2 -340006 m2) for the period.